2020
DOI: 10.1016/j.ijresmar.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Hubristic pride & prejudice: The effects of hubristic pride on negative word-of-mouth

Abstract: Prior research has demonstrated how negative emotions influence negative word-ofmouth (NWOM). However, what if there exist certain positive emotions that influence consumers to spread NWOM? This research develops and tests a novel prediction that shows how a discrete positive emotion-hubristic pride-can increase intention to engage in NWOM following a service failure. Results from six experiments support this prediction. Further, this research shows that psychological entitlement drives the effect of hubristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 86 publications
1
27
0
6
Order By: Relevance
“…In fact, in online interactions facial mimicry does not seem to be crucial for emotional contagion. When interacting online, people associate positive reviews or high ratings with positive emotions, while low ratings and negative reviews are associated with negative emotions (Lindquist et al, 2016;Septianto et al, 2020;Xu et al, 2020). Therefore, emotions shared by others influence customer experience, which results in a specific behavioral response.…”
Section: Emotional Contagion In Behavioral Reactionsmentioning
confidence: 99%
“…In fact, in online interactions facial mimicry does not seem to be crucial for emotional contagion. When interacting online, people associate positive reviews or high ratings with positive emotions, while low ratings and negative reviews are associated with negative emotions (Lindquist et al, 2016;Septianto et al, 2020;Xu et al, 2020). Therefore, emotions shared by others influence customer experience, which results in a specific behavioral response.…”
Section: Emotional Contagion In Behavioral Reactionsmentioning
confidence: 99%
“…"I am successful because I am great"; Tracy and Robins, 2007). Previous research has shown that these two facets of pride can affect consumers' preference for luxury brands (McFerran et al, 2014), motivation for delayed gratification (Ho et al, 2016), processing of product information (Yang and Zhang, 2018) and negative word-of-mouth behavior (Septianto et al, 2020). This present study extends this line of research by exploring how these two facets of pride influence consumers' brand attitudes toward brands associated with dissociative outgroups.…”
Section: Introductionmentioning
confidence: 52%
“…Yang and Zhang (2018) showed that authentic pride (hubristic pride) activates local (global) cognitive appraisal tendencies and consequently makes consumers put more weight on product feasibility (desirability) attributes. Septianto et al (2020) showed that hubristic pride (vs authentic pride) can increase consumers' intention to engage in negative word-of-mouth after a service failure. In the current research, we extend these previous consumer research studies on authentic pride and hubristic pride by investigating how these two facets of pride can influence consumers' brand attitudes toward brands associated with dissociative out-groups.…”
Section: Pride and Consumer Behaviormentioning
confidence: 99%
“…As manipulation checks, participants indicated whether they agree that the restaurant was socially irresponsible (1 = strongly disagree, 7 = strongly agree). They also indicated whether the restaurant expressed different emotions about their action ("anger," "sadness," "disappointment," "regret," "guilt," and "shame"), measured on a 7-point scale (1 = not at all, 7 = very much) (adapted from Septianto, Northey, et al, 2020).…”
Section: Procedures and Measuresmentioning
confidence: 99%